Brain correlates of impaired goal management in bipolar mania. Issue 3 (5th February 2023) - Madre, Mercé; Fuentes-Claramonte, Paola; Palau, Pol; Sáez, Naia; Moro, Noemí; Blanch, Clara; Verdolini, Norma; Garcia-Leon, Maria Angeles; Feria, Isabel; Munuera, Josep; Sarró, Salvador; Raduà, Joaquim; et al.
Abstract: Background: Although executive impairment has been reported in mania, its brain functional correlates have been relatively little studied. This study examined goal management, believed to be more closely related to executive impairment in daily life than other executive tasks, using a novel functional magnetic resonance imaging (fMRI) paradigm in patients in this illness phase. Methods: Twenty-one currently manic patients with bipolar disorder and 30 matched healthy controls were scanned while performing the Computerized Multiple Elements Test (CMET). This requires participants to sequentially play four simple games, with transition between games being made either voluntarily (executive condition) or automatically (control condition). Results: CMET performance was impaired in the manic patients compared to the healthy controls. Manic patients failed to increase activation in the lateral frontal, cingulate and inferior parietal cortex when the executive demands of the task increased, while this increase was observed in the healthy controls. Activity in these regions was associated with task performance. Conclusions: Manic patients show evidence of impaired goal management, which is associated with a pattern of reduced medial and lateral frontal and parietal activity.